Strategi TPKS Dalam Mempertahankan Kinerja B/M Petikemas Dalam Masa Pandemi Covid-19 - Ridwan Ridwan; M. Aji Luhur Pambudi (Sekolah Tinggi Maritim Yogyakarta, 2022)
The Corona Virus Pandemic period has an effect on the whole world, including in Indonesia in 2020. With the spread of the corona virus, it can also have an impact on reducing the performance of loading and unloading containers. With the Covid-19 pandemic, the management of the Semarang container terminal made several changes, additions and evaluations to maintain the performance of container loading and unloading. The method used in this study is a qualitative and quantifiable method that refers to data on the flow of loading and unloading at the Semarang Container Terminal. Therefore, it is hoped that this study can find out the strategy used by the Semarang Container Terminal to maintain loading and unloading performance during the Covid-19 pandemic by developing the dock area, stacking field, adding infrastructure, making several strategic programs, as well as preparing systems and procedures in providing guidelines and procedures for container services that include loading and unloading services.